HPLC Separation of Phenolic Acids on Silica Gels Layer-by-Layer Modified with 6,10-Ionene and Dextran Sulfate - A. N. Ioutsi (Journal of Chemistry)
Using phenolic acids as an example, we continue to study the nature of the previously obtained multilayer sorbents for HPLC—silica gels modified up to two times with 6,10-ionene and dextran sulfate (DS). The chromatographic behavior of this class of compounds on the obtained sorbents was studied. A six-component mixture of sorbic, vanillic, sinapic, p-coumaric, caffeic, and ferulic acids was separated on the silica gel twice modified with 6,10-ionene and dextran sulfate in 15 min with a selectivity of up to 1.88 and a column efficiency of up to 26000 theoretical plates per meter. The possibility of separating the two classes of compounds—phenolic acids and basic nitrogen-containing pharmaceuticals—in a single mixture on silica gel, twice modified with 6,10-ionene and dextran sulfate, is shown.